Simulation study of liquid desiccant dehumidification system - Toh, Chee How. (2012)
Liquid Desiccant Dehumidification system had proven to be more efficient in removing humidity in the air with a consumption of lesser energy as compared to conventional vapor compression system. The temperature control of the liquid desiccant solution; lithium chloride used in this project is very important as it had a great impact on the performance of the system during dehumidification process. A simulation study had to be done in order to develop a PID control algorithm that is able to control the temperature of the air conditioner which involves in the cooling of the temperature of the liquid desiccant to the pre-set temperature. In this report, it is going to discuss about the installation of the system, followed by experimental processes and procedure in order to obtain data for simulation purposes. Application of empirical modeling methods for process identification and Ziegler-Nichols Step response method is being applied to using the acquired data, the results are later verified through simulations by using MATLAB simulink.